Determinants of accounting fraud with unethical behavior as an intervening variable in OPD Palembang city government - Meilansari, Selvita; Ofasari, Dian; Nurpratiwi, Tiara (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2025)
This study focuses to analyze the effect of internal control, conformity of compensation, information asymmetry and compliance to accounting standards on accounting fraud with unethical behavior as intervening variable in Palembang. This study uses 253 employees of government agencies in Palembang. Primary data is used and processed through structural equation model (SEM) using smartPLS.The result shows that internal control and conformity of compensation have negative and significant effect on unethical behavior, information asymmetry and compliance to accounting standard have positive effect on unethical behavior. However information asymmetry is found to be insignificant. Furthermore, conformity of compensation, information asymmetry and compliance to accounting shows negative and significant effect on accounting fraud meanwhile internal control have positive and insignificant effect. Unethical behavior is found to have positive and significant effect on accounting fraud. The result of sobel test shows that unethical behavior cannot mediate the relationship between internal control, conformity of compensation and compliance to accounting standards on accounting fraud while unethical behavior is also find cannot mediate the effect between information asymmetry on the accounting fraud.